The Confiscated Library of William Macintosh in the Bibliothèque Municipale d'Avignon. (10th June 2021) - Keighren, Innes M
Abstract: In 1795, the private library of William Macintosh, author of Travels in Europe, Asia, and Africa (1782), was seized from his home in Avignon by the revolutionary authorities. Using the inventory of this seizure as a guide, this note presents a reconstruction of Macintosh's library and identifies those books that exist today in the collections of the Bibliothèque municipale d'Avignon.